Correlation of Quality of Life with Palliative Care Needs in Cancer Patients in General Public Hospital Sanglah Denpasar - I Putu Wira Pradana (Coping: Community of Publishing in Nursing, 2013)
Cancer is a chronic disease with high mortality. Cancer patients will experience various problems such as physical, psychosocial, and spiritual which will affecting the quality of life of patients. A way to improve the quality of life is to provide palliative care. Palliative care is an integrated care that includes pain and symptoms management, psychological, and spiritual support. The aim of this study was to determine the relationship of quality of life with palliative care needs in cancer patients in Sanglah Hospital Denpasar. This study was a correlational study with a cross-sectional approach. Sample consisted of 85 cancer patients were selected by purposive sampling, given questionnaire EORTC QLQ-C30 version 3 to assess the quality of life and NEST to assess the needs of palliative care. The Spearman Rank test showed significant values (p) = 0.000 which is smaller than ? = 0.05 (5%). Coefficient correlation values was found at 0.824 with negative values, this indicating the relationship between variables is very strong. It can be concluded that there is a very strong inverse correlation between the quality of life with palliative care needs in cancer patients.